2010
DOI: 10.1128/aem.00666-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Biosynthetic Gene Cluster for 3-Methylarginine, a Toxin Produced by Pseudomonas syringae pv. syringae 22d/93

Abstract: The epiphyte Pseudomonas syringae pv. syringae 22d/93 (Pss22d) produces the rare amino acid 3-methylarginine (MeArg), which is highly active against the closely related soybean pathogen Pseudomonas syringae pv. glycinea. Since these pathogens compete for the same habitat, Pss22d is a promising candidate for biocontrol of P. syringae pv. glycinea. The MeArg biosynthesis gene cluster codes for the S-adenosylmethionine (SAM)-dependent methyltransferase MrsA, the putative aminotransferase MrsB, and the amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
23
0
2
Order By: Relevance
“…While xantholysin does not exert a growth-inhibitory effect on fellow pseudomonads, P. putida BW11M1 also produces a plant lectin-like bacteriocin to target other pseudomonads, including members of the P. syringae group [35], [63], indicating that both ribosomally and non-ribosomally synthesized antimicrobials are part of its armory deployed against competitors. Antagonism among plant-associated γ-proteobacterial relatives has been described for some other types of pseudomonad secondary metabolites: the modified amino acid 3-methylarginine causing inhibition between P. syringae pathovars [64]; the salicylate-containing P. putida antibiotic promysalin, targeting other pseudomonads [65]; oxyvinylglycines active against Erwinia amylovora [66], [67]. In view of the structural similarity of xantholysins to certain pseudomonad lipopeptides with antiviral activity (viz.…”
Section: General Conclusionmentioning
confidence: 99%
“…While xantholysin does not exert a growth-inhibitory effect on fellow pseudomonads, P. putida BW11M1 also produces a plant lectin-like bacteriocin to target other pseudomonads, including members of the P. syringae group [35], [63], indicating that both ribosomally and non-ribosomally synthesized antimicrobials are part of its armory deployed against competitors. Antagonism among plant-associated γ-proteobacterial relatives has been described for some other types of pseudomonad secondary metabolites: the modified amino acid 3-methylarginine causing inhibition between P. syringae pathovars [64]; the salicylate-containing P. putida antibiotic promysalin, targeting other pseudomonads [65]; oxyvinylglycines active against Erwinia amylovora [66], [67]. In view of the structural similarity of xantholysins to certain pseudomonad lipopeptides with antiviral activity (viz.…”
Section: General Conclusionmentioning
confidence: 99%
“…A biosynthesis study demonstrated that three clustered genes, mrsA, mrsB, and mrsC, can produce ␤-methylarginine in Escherichia coli. A catalytic assay of MrsA, a methyltransferase, can convert 5-guanidino-2-oxo-pentanoic acid into 5-guanidino-3-methyl-2-oxo-pentanoic acid in vitro (8). The resulting product was proposed as a promising substrate for MrsB, an aminotransferase, to give the final product ␤-methylarginine, which was discharged from the cell by the exporter MrsC.…”
mentioning
confidence: 99%
“…Structure of (5S,6S)-aminotenuazonic acid (1a)a nd (5S,6S)-tenuazonic acid (2). Only the predominant tautomeric form in neutral solution is depicted. the [M+ +H] + ion at m/z 213.12364, which are both in agreement with the molecular formula C 10 H 16 O 3 N 2 for 1a.T he presence of ten carbonsi nt he 13 CNMR spectrum confirms the molecular formula, whereas the 1 HNMR spectrum recorded at 300 Ki nD 2 Oe xhibits twelve nonexchangeable protons in total. Consequently, 1a contains four exchangeable protons.…”
Section: Resultsmentioning
confidence: 74%
“…(2S,3S)-3-Methylornithine (4)m ight be derived from l-ornithine (3)b yt ransamination, yieldingt he corresponding 2-oxo acid, followed by methylation with S-adenosylmethionine (SAM) and subsequent transamination to compound 4 analogously to the biosynthesis of 3-methylarginine in Pseudomonas syringae. [13] (2S,3S)-3-Methylornithine (4) might react with activateda cetoacetatet ot he intermediate Nacetoacetyl-(2S,3S)-3-methylornithine (5). Subsequentc yclisation would finally yield compound 1a (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation